ANALISIS PERILAKU PENCEGAHAN KEPUTIHAN PATOLOGI PADA REMAJA PUTRI DI KABUPATEN DEMAK - Sri Mularsih; Dewi Elliana (Jurnal Ilmiah Maternal, 2019)
ABSTRACT According to (WHO), women rarely pay attention to cleanliness in their external genital organs. Infec- tion in the vagina each year attacks women around the world 10-15% of 100 million women, adolescents affected by candida bacterial infections about 15% and experiencing vaginal discharge. The incident was due to adolescents not knowing the problems surrounding reproductive organs. In Indonesia around 90% of women have the potential to experience vaginal discharge because the country of Indonesia is a tropical climate, so the fungus is easy to develop resulting in many cases of vaginal discharge in Demak Regency the number of teenagers experiencing vaginal discharge is 29.8 % (22,797 people) both physiological and pathological vaginal discharge. The purpose of this study was to analyze the relationship between the level of knowledge about vaginal discharge with pathology prevention behavior in young women in Saka Bhakti Husada Demak III Health Center, Demak Regency. This study used a cross sectional design and used a total sampling technique. The population in this study was all 32 female teenagers from Saka Bhakti Husada Demak Health Center, Demak District, and the sam- pling technique was saturated sampling. The results of the study are that the knowledge about vaginal dis- charge most of the respondents have sufficient level of knowledge 25 (78.1%) respondents, and the behavior of preventing vaginal discharge pathology most of the respondents have positive behavior of 31 (96.9%) respondents. And there is a relationship of knowledge about leucorrhoea with pathology prevention behavior of vaginal discharge in young women with p value 0.007 ≤0.05. Midwife advice should increase efforts in providing services and complete and accurate information about vaginal discharge and how to prevent it. Keywords: Leucorrhoea Knowledge, Behavior prevent pathological leucorrhoea ABSTRAK Menurut (WHO), perempuan jarang dalam memperhatikan kebersihan pada organ genitalia eksternanya. Infeksi pada vagina setiap tahunnya menyerang perempuan di seluruh dunia 10-15% dari 100 juta perem- puan, remaja yang terkena infeksi bakteri kandida sekitar 15% dan mengalami keputihan. Kejadian tersebut dikarenakan remaja tidak mengetahui permasalahan seputar organ reproduksi.Di Indonesia sekitar 90% wan- ita berpotensi mengalami keputihan karena negara Indonesia adalah daerah yang beriklim tropis, sehingga jamur mudah berkembang yang mengakibatkan banyaknya kasus keputihan Di Kabupaten Demak angka remaja yang mengalami keputihan sebesar 29,8% (22.797 orang) baik keputihan fisiologi maupun patologi. Tujuan dari penelitian ini adalah untuk menganalisis hubungan tingkat pengetahuan tentang keputihan den- gan perilaku pencegahan keputihan patologi pada remaja putri di Saka Bhakti Husada Puskesmas Demak III Kabupaten Demak. Penelitian ini menggunakan rancangan Cross Sectional dan menggunakan tehnik sampling tehnik total sam- pling.Populasi dalam penelitian ini yaitu seluruh remaja putri Saka Bhakti Husada Puskesmas Demak III Kabupaten Demak sejumlah 32 orang dengan tehnik pengambilan sampel adalah sampel jenuh. Hasil peneli- tian adalah bahwa pengetahuan tentang keputihan sebagian besar responden memiliki tingkat pengetahuan yang cukup 25 (78,1%) responden, dan perilaku mencegah keputihan patologi sebagian besar responden memiliki perilaku positif sejumlah 31 ( 96,9%) responden.Dan ada hubungan pengetahuan tentang keputihan dengan perilaku pencegahan keputihan patologi pada remaja putri dengan p value 0,007≤0,05.Saran bidan seharusnya meningkatkan upaya dalam memberikan pelayanan dan informasi yang lengkap dan akurat ten- tang keputihan dan cara mencegahnya. Kata Kunci: Pengetahuan Keputihan, Perilaku mencegah keputihan patologis